A newly-designed free-standing NiCo2O4 nanosheet array as effective mediator to activate peroxymonosulfate for rapid degradation of emerging organic pollutant with high concentration. (November 2022) - Cong, Yanqing; Chen, Xiang; Ye, Lingjie; Li, Xuchun; Lv, Shi-Wen
Abstract: Nowadays effective treatment of high concentration organic wastewater is still a formidable task facing human beings. Herein, for the first time, a well-defined ZIF-67-derived NiCo2 O4 nanosheet array was successfully prepared by a feasible method. In comparison with ordinary NiCo2 O4 nanosphere, the formation of nanosheet structure could offer more opportunities to exposure internal active sites of NiCo2 O4, thereby resulting in smaller interface resistance and higher charge transfer efficiency. As expected, ZIF-67-derived NiCo2 O4 nanosheet array displayed great performance in peroxymonosulfate (PMS) activation. More importantly, recyclable redox couples of Co 3+ /Co 2+ and Ni 3+ /Ni 2+ endowed the stable catalytic activity of NiCo2 O4 nanosheet. Interestingly, developed NiCo2 O4 -1/PMS oxidation system could achieve the effective degradation of antibiotics with high concentration in a short time. Both radical and nonradical pathways were involved into PMS activation, wherein SO4 −, OH, O2 − and 1 O2 were major reactive oxygen species. The formation paths of reactive oxygen species and effects of inorganic anions were also investigated. Electrochemical analyses revealed that NiCo2 O4 -1 with nanosheet structure mediated the electron transfer between PMS and tetracycline (TC), which played a vital role in TC degradation. Furthermore, developed NiCo2 O4 -1/PMS oxidation system displayed great removal ability towards TC in actual water samples, and degradation products were low toxicity or no toxicity. In short, current work not only developed an effective oxidation system for completing the rapid degradation of antibiotic with high concentration, but also shared some novel insights into the activation mechanism of SR-AOPs. Graphical abstract: Image 1 Highlights: Nanosheet structure can reduce the interface resistance and boost the charge transfer. Recyclable redox couples of Co 3+ /Co 2+ and Ni 3+ /Ni 2+ endowed stable catalytic activity. The formation paths of reactive oxygen species were proposed. Direct electron transfer played a vital role in pollutant degradation. High-concentration antibiotic can be rapidly degraded by NiCo2 O4 /PMS oxidation system.